Load Distribution On The Expansion Of The Medium Voltage Distribution Network From Single Phase To Three Phase In Gondorio Using Etap 12.0 - Enda Wista Sinuraya; Aris Triwiyatno; Bambang Winardi; arnoto arnoto (PT. Banjarese Pacific Indonesia, 2025)
The Gondoriyo 1-phase network has a network length of 3.2 km supplied by a 1-phase network that is charged in phase S on BSB 1. The extent of the service area makes the load on phase S jump high. The measurement results obtained by the load current during peak load reached a total of 62A. While the load current of the repeater at the time of peak load is phase R of 32A, phase S of 98A, and phase T of 44A. With such conditions, it is necessary to expand the medium voltage distribution network in the Gondoriyo area with the aim of balancing the load on the BSB 1 extension. To facilitate load sharing in the expansion of the Gondoriyo area, the ETAP powerstaion 7.5.0 simulation program is used. which consists of 1 phase simulation before expansion and 3 phase simulation after expansion. From the results of this engineering shrinkage simulation, the total engineering shrinkage value in the 1-phase network before the expansion was 6480 kW, after the network expansion, the total engineering shrinkage changed to 2510.4 kW. With the simulation that has been made, it is expected to produce a load sharing plan that will make it easier for PT PLN (Persero) Rayon Boja to share the load on the network after the expansion.